KARAKTERISTIK FENOTIPE BEBERAPA SIFAT KUANTITATIF AYAM KAMPUNG DI MINAHASA - Milas, Ezri S.S.; Saerang, Josephine L.P.; Lambey, Lucia J.; Takaendengan, Ben J. (ZOOTEC, 2020)
PHENOTYPE CHARACTERISTICS OF SOME QUANTITATIVE TRAITS OF NATIVE CHICKEN IN MINAHASA. This study aims to obtain a measure of the phenotypic character of the quantitative traits of native chickens in Minahasa, North Sulawesi. This research was useful as additional information about the quantitative character of native chickens in Minahasa as a reference in efforts to preserve genetic resources (SDG) both for the development of native chickens and other breeding purposes. The material used was 291 male and female native chickens that had been separated by age (6 months and above) and had reached adult sex in the Minahasa Regency. The research method used was descriptive analysis (average, standard deviation, coefficient of variation and correlation) and continued withT-test. Retrieval of data by direct observation and measurement of quantitative properties based on the observed parameters. The results of this study illustrate the phenotypic character of quantitative traits of male and female native chickens in Minahasa where the size of the FL (femur length) and WL (wing length) were not different or the same in both sexes. SC (shank circumference) and CL (comb length)   were     significantly  different (P<0.05), while the trait of TL (tibia length), SL (shank length), TFL (third finger length), CH (comb height) showed differences very significant (P<0.01). It can be concluded quatitavive characteristics of native chicken in Minahasa were diverse and correlate from high to low.Keywords: native chicken, phenotype, quantitative characteristics.